Observation of a Current Plateau in the Transfer Characteristics of InGaN/AlGaN/AlN/GaN Heterojunction Field Effect Transistors - 闫俊达 王权 王晓亮 肖红领 姜丽娟 殷海波 冯春 王翠梅 渠慎奇 巩稼民 张博 李百泉 王占国 侯洵 (Chinese physics letters, 2015)
Direct-current transfer characteristics of （InGaN）/A1GaN/A1N/GaN heterojunction field effect transistors （HFETs） are presented. A drain current plateau （IDs = 32.0 mA/mm） for Vcs swept from ＋0.7 V to -0. 6 V is present in the transfer characteristics of InGaN/AIGaN/AIN/GaN HFETs. The theoretical calculation shows the coexistence of two-dimensional electron gas （2DEG） and two-dimensional hole gas （2DHG） in InGaN/AIGaN/A1N/GaN heterostructures, and the screening effect of 2DHG to the 2DEG in the conduction channel can explain this current plateau. Moreover, the current plateau shows the time-dependent behavior when IDs Vcs scans repeated are conducted. The obtained insight provides indication for the design in the fabrication of GaN-based super HFETs.